WORKING TIME EFFICIENCY AND FACILITIES UTILIZATION OF PT. PROSKUNEO KADARUSMAN SHIPYARD MUARA BARU JAKARTA - Zamira, Nasywa Aurellia; Apriliani, Izza Mahdiana; Zahidah; Putra, Pringgo Kusuma Dwi Noor Yadi; Pratama, Gilar Budi (Departemen PSP IPB, 2025)
Shipyard is one of the port facilities that serves as a means of maintaining the ship before returning to fishing activities. PT. Proskuneo Kadarusman shipyard needs to maintain its existence in order to remain the shipyard of choice for ship owners through the speed of processing time of the services provided. This research aims to determine the most efficient time in the ship repair process at PT. Proskuneo Kadarusman shipyard. This research was conducted in January 2025 using a case study method of fishing vessel repair activities based at PPS Nizam Zachman Jakarta. The data obtained was then analyzed through a network with the critical path method and to identify the level of utilization of its facilities. The results showed that routine maintenance or minor repairs of fishing vessels and repairs accompanied by engine repairs can be completed within 4 days with an effectiveness of 66.67% of the time allocated by the shipyard. The utilization level of shipyard facilities from 30 GT fishing vessel repair activities is worth 66.67-100% which that the utilization of the work area is optimal. Factors that affecting ship repair work time are the condition of shipyard facilities, material availability, and the level of ship damage. Key words: critical path method, fishing vessel, network analysis, ship repair